Analysis of UAV-Photogrammetry for the Spatiotemporal Monitoring of Pavement Elevation in a Rural Road - Helik Susilo; Martince N Bani; Muhammad Tri Aditya; Dyah A.R Cupasindy; Fuji Asema (Westscience Press, 2025)
Unmanned Aerial Vehicle (UAV) photogrammetry has gained significant popularity across various industries due to its versatility in a wide range of applications. In the field of surveying, UAV photogrammetry offers a faster and more cost-effective solution compared to surveying conventional methods such as leveling instruments or total stations. In rural areas, the pavement of village access roads is vulnerable to deterioration, particularly in the form of settlement caused by repeated loads from transport vehicles. Therefore, monitoring pavement settlement is essential to ensure safety and facilitate timely maintenance planning. Mostly, pavement settlement measurements are conducted using conventional surveying methods. This study aims to explore the potential of UAV-photogrammetry in monitoring pavement elevation in rural areas and to assess its accuracy compared to conventional surveying methods. Aerial data acquisition was conducted in two separate epochs: Epoch I on December 18, 2024, and Epoch II on April 23, 2025. These multitemporal aerial surveys produced a series of overlapping aerial photos. Within the study area, point markers were installed as reference points for elevation measurements on the generated Digital Elevation Model (DEM). The elevation change from Epoch I to Epoch II ranged from 0.00 to 0.029 meters. However, this change cannot be directly interpreted as pavement deformation or settlement. This limitation arises because the root mean square error (RMSE) values of the elevation data obtained from UAV photogrammetry and total station measurements range from 0.048 to 0.098 meters.